Re-playing Legends’ Worlds: Toying with Star Wars’ Expanded Universe in Adult Play - Katriina Heljakka (My University, 2022)
In this essay, I describe how adult fans of the Star Wars universe engage actively in worldbuilding through world-play. What distinguishes world-play from world-building, as proposed by Wolf (2012), is an understanding that adult toy play involves more than mere collection of toys, the most prominent concept in both hobbyist and theoretical writings on adults’ relationships with toys. In my analyses of visual and narrative data collected with adults, I have concentrated on profiling the types of adults who play with toys (Heljakka, 2013) and mapping out popular play patterns and motivations to play in reference to mass-produced toys (e.g., Heljakka, 2012; 2013; 2015). The essay at hand aims to investigate how adults’ play with Star Wars toys also entails elements of world-building in terms of both imaginative and spatially emerging object play patterns. Moreover, my study explores the employment of narratives from the original Star Wars films as texts and a source for contemporary fan play. Focus will be given to how the story-worlds of George Lucas, now imagined further by Disney and its storytellers, impact the current world-playing practices of Star Wars fans.